The Quality Improvement of Certified Teachers’ Teaching Performance Using the Deming Cycle Model - Andreas Andreas; Reinhard Leonardo Paais (Universitas Kristen Satya Wacana, 2026)
Teacher performance enhancement is vital for optimal education quality. This research portrays the Deming Cycle’s application in improving certified teachers' performance at SMK Negeri 1 Sorong Regency. Using a qualitative descriptive approach, data were gathered from a principal and 13 purposively selected teachers through interviews, observations, and FGDs. Data were validated via triangulation and analyzed using Miles and Huberman’s interactive model. Results indicate that the Deming Cycle (PDCA) effectively enhances teaching performance. The Plan step identified needs for innovation, while the Do step implemented Project-Based Learning (PjBL) to boost students' analytical and creative skills. The Check step showed significant growth in teacher confidence and student engagement. Finally, the Act stage established sustainable mentoring and collaboration. Practically, the Deming Cycle serves as a